Development of a DoE with a new electrospinning system for cartilage tissue engineering - Silva, E. (2022)
Electrospinning is currently one of the most used techniques to produce fibrous synthetic tissues such as cartilage and bone. To replicate cartilage tissue engineering functionality, one of the most important characteristics is the alignment of the resulting fibre meshes in a three-dimensional (3D) fashion. Here, a newly developed electrospinning collector system is tested in order to understand how the process parameters affected the obtained fibre meshes topography. For that, a polymer consisting of PCL/Gelatin was electrospun using the electrostatic potential to create a fibre mesh. A Design of the Experiments (DoE) approach was implemented, to determine whether the variation of the main process parameters led to significant effects on the mesh dimensional characteristics. The process parameters analyzed were the velocity of the collecting bands, the linear velocity of the fibre deposition table and the flow rate. The analyzed mesh characteristics were the fibre diameter, the distance between the fibres and pore size. The effect of each of the three factors was statistically analyzed using ANOVA, as well as the interaction between them. Complementary an ANOVA linear regression approach was developed to predict the distance between the fibres. This statistical regression was then compared with a predictive theoretical model and with the experimental results. The results obtained indicate the presence of interactions between the three process parameters analyzed. The three process parameters showed statistical significance in the distance between the fibres, however, the velocity of the deposition table was the process parameter that presented the highest effect.